Performance Analysis of Power Consumption in LTE-A eNB and its Effect on the Overall System Efficiency - Eric Nii Sackey; Eric Sackey (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Machine-to-Machine (M2M) communication over the Long Term Evolution Advanced (LTE-A) networks has witness exponential growth and expansion in the last couple of years. This expansion has created an increase in the demand for high speed internet, multimedia messaging services, digital broadcasting etc, thus fuelling higher data traffic. The network operators in trying to meet this increasing demand injected more access points by deploying more Base Stations (BSs) to make the network denser. The BSs are the major consumers of energy in the wireless communication network due to the use of inefficient power amplifiers and therefore deploying more BSs into the network will increase the power consumption and the networks operational cost. The aim of this paper was to examine the power consumption patterns of the main elements in the BS, employ various techniques to reduce their power consumption, reduce the operational cost and improve the efficiency of the BS.